(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
In this work the data of methylene blue (MB) and Hoechst 33258 interaction with DNA are presented. It has been shown that at 0.002 M ionic strength of solution MB is bound to double-stranded DNA by three modes: intercalation, semi-intercalation and electrostatic. It was revealed that at higher ionic strengths of solution complete intercalation of MB becomes thermodynamically unacceptable. It was shown that Hoechst 33258 was bound to DNA by two types – “strong” and “weak”. It was also shown that the “strong” type of Hoechst 33258 binding depends on solution ionic strength.